ANALISIS VARIABEL KEBERHASILAN KUD (Studi Kasus di KUD Kabupaten Musi Banyuasin, Sumatera Selatan) - BAIDOWI - -; Agus - Suman; M. Umar - Burhan (Sekolah Pascasarjana Universitas Brawijaya, 2009)
ABSTRACT The aims of this research are to determine (1) the effect of variables to the success of cooperation in achieving an autonomous village cooperative; (2) to determine which of the seven variables has the strongest effect on the success of the village cooperative. This research was mainly on the village cooperatives running in providing food and distributing production tools such as fertilizer, pesticide, prime seeds, and so on, in the Musi Banyuasin regency, South Sumatra province. The research location was determined based on the fact that the Musi Banyuasin Regency is one of the regencies located in South Sumatera which succeeded in developing the autonomous village cooperative. Sampling was applied to the village cooperatives which had been operating for more than two years and had corporate body at the time of investigation. As many as 47 autonomous village cooperatives were selected from the 147 available in the Musi Banyuasin regency. A village cooperative is considered autonomous if it has fulfilled the 13 criteria of the Department of Cooperative. To measure the success of the cooperative, several indicators are used, they are Profit Margin, Liquidity Ratio, and Solvability Ratio. The variables influencing the success of the village cooperative in becoming an autonomous cooperative are member’s participation, operation volume, the board’s education, board’s experience, capital growth, business variation and service of the village cooperative involved. The regression and regression coefficient test simultaneously showed highly significant influence on the indicators of profit margin, liquidity and solvability. This means that the suggested variables statistically determined toward the success of the village cooperative. The t-significance at a=1% showed that two variables highly influenced the success of the village cooperative, they were the operation volume and capital growth. This fulfils the autonomous cooperative criteria: the total operation volume has to be in proportion with the number of members and the capital equity has to be at least 25 million rupiah. This indicates that the core of success for the village cooperative rests on the operation volume and the capital growth: the higher the operation volume and capital growth, the better the marketing and financial performance of the village cooperative. From the management handling perspective, it is indicated that the higher the board’s education and the longer the experience, the higher the success of the village cooperative. Keywords: village cooperative.